Compliance with code of corporate governance (2005) in remuneration matters for directors and top five executives. - Chia, Shuang An. (2012)
There is an increasing trend of amounts being paid to directors and executives. Many often question if the remuneration paid is indeed justifiable. The amount of disclosure that companies provide in this area would help in this assessment. One of the key concerns of shareholders is directors’ remuneration being excessive. This study examines the level of disclosure on remuneration matters of SGX-listed companies in compliance to requirements set out by the Code of Corporate Governance 2005. 2011 Annual Reports of 240 companies were used in the study. Analysis was done on the general level of disclosure for listed companies, between SGX Mainboard and Catalist companies, and between different sectors. It was found the level of disclosures is of a satisfactory standard with a few areas that can be improved on. It is also noted that the level of disclosure of SGX-listed companies is still far behind other developed countries; it might be worthy to ensure that compliance with the Code is made compulsory.